Contextualized School-Based Cognitive Behavioral Therapy (CBT) Intervention for Malaysian Secondary School Students - Saw, Jo Anne; Tam, Cai Lian; Thanzami, Vanlal; Bonn, Gregory (Frontiers in Psychiatry, 2020)
This study investigates the effectiveness of the school-based Shine Through Any Roadblocks (STAR) CBT intervention, by a screening conducted on 634 students from eight secondary schools in Malaysia. The participants (n = 85) who fulfilled the eligibility criteria in the screening were assigned randomly to either the intervention group (n = 42) or the assessment-only waitlist control group (n = 43). The intervention consisted of eight-sessions over the period of two months, each conducted for 60 minutes in group-based modality according to the module. Moreover, the outcome measures (depressive symptoms and automatic negative thoughts) were administered at five-time intervals, which are the baseline/pre-intervention, mid-intervention, post-intervention, one-month follow-up after intervention, and three-month follow-up after intervention, resulting in significant and consistent lower levels of outcome measures among the intervention group. Therefore, it was indicated that the adapted Malaysian CBT protocol is possibly a successful method of reducing depressive symptomatology among adolescents. Clinical implications were further discussed for better prevention and treatment for depression as a school-based intervention in Malaysia.